The impact of successful chronic total occlusion percutaneous coronary intervention on clinical outcomes: a tertiary single-center analysis - Will, Maximilian; Schwarz, Konstantin; Aufhauser, Simone; Leibundgut, Gregor; Schmidt, Elisabeth; Mayer, David; Vock, Paul; Borovac, Josip A.; Kwok, Chun Shing; Lamm, Gudrun; Mascherbauer, Julia; Weiss, Thomas (Frontiers in Cardiovascular Medicine, 2024)
Background The benefit of chronic total occlusion (CTO)-percutaneous coronary intervention (PCI) is controversial because of a lack of high-quality evidence. We aim to evaluate the impact of CTO-PCI on symptoms, quality of life and mortality. Methods We conducted a retrospective single center study of patients with CTO-PCI in a tertiary center in Austria. The study outcomes were Canadian Cardiovascular Society (CCS) angina score, quality of life measured by Seattle Angina Questionnaire (SAQ), and death at median follow up for patients with successful vs. failed CTO-PCI. Results A total of 300 patients underwent CTO-PCI for coronary artery disease, of which 252 (84%) were technically successful with median follow up of 3.4 years. There were no significant differences in in-hospital or all-cause mortality, major adverse cardiovascular event, or stent-related complications between the groups of failed and successful CTO-PCI. Among patients with successful CTO-PCI there was a significant improvement in CCS score, which was not found for the group with failed CTO-PCI. Successful reopening was associated with significant benefits of the SAQ domains of angina with stressful activity [3.7 ± 0.9 vs. 3.1 ± 0.5, p = 0.004, use of nitrates (4.7 ± 0.5 vs. 3.0 ± 1.0) p = 0.005] and satisfaction from angina relief (4.4 ± 1.1 vs. 3.6 ± 1.4 p < 0.001). Conclusion While there was no significant difference in mortality, successful CTO-PCI was associated with greater reduction in angina and the use of nitrates compared to unsuccessful CTO-PCI.